ChemInform Abstract: Utilization of Acidic α‐Amino Acids as Acyl Donors: An Effective Stereo‐Controllable Synthesis of Aryl‐Keto α‐Amino Acids and Their Derivatives. Issue 41 (7th October 2014) - Wang, Lei; Murai, Yuta; Yoshida, Takuma; Okamoto, Masashi; Tachrim, Zetryana Puteri; Hashidoko, Yasuyuki; Hashimoto, Makoto
Abstract Review: 83 refs.